THE TECHNIQUE OF TEACHING VOCABULARY USING PICTURE POCKET GAME TO ENRICH ELEMENTARY-AGE STUDENTS’ VOCABULARY - Irma Wahyuni; Fadhilah Najmee Amroo (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2019)
The main objective of this research is to investigate the technique of teaching vocabulary in English learning using picture pocket game to enrich elementary[1]age students' vocabulary in the classroom. This research was taken at 3 elementary schools, namely SDN Cibatok 03, SDS Al-Husna Leuwiliang and SDIT Bumi Putera Pamijahan. The method of this research is qualitative descriptive method that using purposive sampling. The instruments of this research used observation, field note, interview and documentation in collecting data. The result of this research shows that picture pocket game was a proper technique of teaching English vocabulary to enrich elementary-age students. Furthermore, the picture pocket game can encourage students’ interest and motivate in learning English, also make a pleasant atmosphere in the classroom. The English vocabulary materials selection given by a teacher through a picture pocket game were adapted to the students' ability and selected according to indicators of students’ language daily use